(untitled) (Annual of the Faculty of Philosophy in Skopje, 2012)
The purpose of this article is to analyze the basic contents of the agitation and propaganda of the Communist Party of Yugoslavia (Macedonia) during the National-liberation war (1941-1944) in the Vardar part of Macedonia. This organized activity, through the printed materials and public speech of the Partys activists, played key role in the planned direction of the accumulated revolutionary s energy of the Macedonian people for the realization of the shortterm and long-term goals of the CPY In the framework of the common Yugoslav matrix, the contents of Party s agitation and propaganda in Macedonia had their specifics, among which the domination of the national over the class component, was the most important.